Mounting pressure on Russia's government budget: Financial and political risks of stagnation - Janis Kluge (Stiftung Wissenschaft und Politik (SWP), 2019)
Economic stagnation and demographic change in Russia are putting intense pressure on the government budget. Tax revenues have been declining since the late 2000s. Meanwhile, the oil dependency of Russia's budget has increased significantly. This became patently clear when the oil price plummeted in 2014. Energy revenues have since begun to recover, but the Finance Ministry's reserves have shrunk considerably and are only slowly being replenished. To keep public budgets stable, the Russian government is forced to raise taxes and extend the retirement age in the years to come. There is a widening gap in funds required to cover the paternalistic social policies of earlier years. At the same time, the struggle for control of public resources is having a destabilizing effect on the political regime - especially in light of the ever more pressing question of Putin's successor in the Kremlin. Up to the presidential election of 2018, the Russian leadership avoided making any budget cuts that would have hurt key clientele groups: retirees and the military-industrial complex. Additional income was generated instead through a series of smaller budgetary adjustments. Shortly after the start of Putin's fourth term, however, tax raises and a higher retirement age were announced, which lead to drastic declines in the president's approval ratings. As a reaction to shrinking funds, budget policy is now being controlled in a more centralized way by Moscow, while public oversight of government budgets has been restricted. Shadow budgets have also emerged outside the purview of the finance administration. In this complex and politically tense situation, conflicts between elites are erupting with increasing frequency, bearing risks for Putin's fourth term in office.
Keywords: 320; Öffentlicher Haushalt; Öffentliche Finanzen; Ölpreis; Russland